A geometria no ciclo de alfabetização : outros olhares a partir do PNAIC 2014 - Francischetti, Elisângela Aparecida (Universidade Federal de São Carlos, 2016)
The present research aims to identify the perceptions of four literacy teachers, based on their own perspective, regarding the received continued formation; identify and analyze pedagogical practices for mathematical literacy from the perspective of literacy; and identify the marks of this formation in relation to the teaching and learning of geometry, as a result of the National Pact for Literacy in the Right Age (PNAIC), in 2014. The methodology of this study is qualitative in nature. Data collection was carried out in two schools of a municipal school network in the interior of São Paulo and consisted in the following instruments: questionnaires and semistructured interviews provided by the teachers, and classroom observations of the pedagogical practices of mathematical literacy, containing the perceptions of the researcher, recorded in a field diary. The research on teacher training was based on the contributions of Nóvoa (1999), Tardif and Raymond (2000), Tardif (2000; 2002), Mizukami et al. (2002), Reali (2009), Imbernón (2010) and Candau (2011). In relation to the teaching of mathematics in the initial years, we considered the studies of Nacarato, Mengali and Passos (2011) and Serrazina (2012) and, regarding the teaching and learning of geometry in the initial years, we referred to the research of Lorenzato (1993), Passos (2000), Pavanello (1989, 1993, 2004), Nacarato and Passos (2003, 2014) and Conti (2015). The results, products of the analysis of the answers emitted by the surveyed teachers, show that from the formations of the PNAIC there was an amplification of teaching practices contextualized in the classes of mathematics, fruit of didactic interventions that stimulated the construction of the mathematical knowledge in a significant way considering the teaching role as a key element of this construction of teaching knowledge. The program also developed, in the teachers, a greater awareness on the importance of the development of geometric thinking since the early years of the literacy cycle, expanding the pedagogical possibilities both in the figural and the conceptual elements. The pertinence of this research is based on the social relevance of the theme, seeking a theoretical deepening on the concepts of mathematical literacy in the perspective of geometry literacy, teaching and learning in the literacy cycle, as well as professional teacher development; thus, collaborating to the development processes of the professional's autonomy and consequently aiming at improving the quality of mathematics teaching in the literacy cycle.
Keywords: Alfabetização matemática; Geometria; Formação continuada de professores; Pacto Nacional pela Alfabetização na Idade Certa (Brasil); Mathematical literacy; Continuing teacher education; Geometry; National Pact for Literacy at the Right Age (PNAIC); CIENCIAS HUMANAS::EDUCACAO::CURRICULO